Stress distribution near a rectangular cut-out in a reinforced circular cylinder due to direct shear loading and torque. part 1, test results - Henson, G. S. (College of Aeronautics, Cranfield, 1952)
A cylindrical reinforces cylinder 18’’ by 100.6 outside diameter, with two horizontally opposed rectangular cut-outs was loaded separately by direct shear and torque. Continues …